2014
DOI: 10.1371/journal.pone.0095003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of DNA Barcode Variation in Canadian Marine Molluscs

Abstract: BackgroundMolluscs are the most diverse marine phylum and this high diversity has resulted in considerable taxonomic problems. Because the number of species in Canadian oceans remains uncertain, there is a need to incorporate molecular methods into species identifications. A 648 base pair segment of the cytochrome c oxidase subunit I gene has proven useful for the identification and discovery of species in many animal lineages. While the utility of DNA barcoding in molluscs has been demonstrated in other studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 53 publications
(57 reference statements)
7
81
0
3
Order By: Relevance
“…A phylogenic tree with all available M. trossuslus mtCOI sequences is shown in Figure 3. Two mtCOI sequences from the DNA barcode study of Layton, Martel, and Hebert (2014), and identified as M. trossulus , clustered with both ours and Metzger et al. (2016) leukemia cell sequences.…”
Section: Example With Our Own Data In Mytilus Musselssupporting
confidence: 80%
See 1 more Smart Citation
“…A phylogenic tree with all available M. trossuslus mtCOI sequences is shown in Figure 3. Two mtCOI sequences from the DNA barcode study of Layton, Martel, and Hebert (2014), and identified as M. trossulus , clustered with both ours and Metzger et al. (2016) leukemia cell sequences.…”
Section: Example With Our Own Data In Mytilus Musselssupporting
confidence: 80%
“…Sequences from chimeric French mussels are depicted with blue circles, neoplastic cell sequences (from Metzger et al., 2016) with red circles, nonneoplastic cell sequences (from Metzger et al., 2016) with black circles, sequences from GenBank with light gray diamonds and sequences from GenBank from Layton et al. (2014) in dark gray diamonds…”
Section: Example With Our Own Data In Mytilus Musselsmentioning
confidence: 99%
“…3). The study that originally published these sequence data used the name L. "alascensis" (Layton et al, 2014). This may in fact be the correct identification for those specimens.…”
mentioning
confidence: 99%
“…et al, 1975) such as cytochrome b oxidase (cyt-b) for tuna (Bartlett , 1991), 16S rRNA for holothurian species (Bergene et al, 1995), cytochrome c oxidase subunit I (COI) for three genera of planktonic copepods (Bucklin et al, 1999)), the ground breaking approach was brought by Hebert et al (2003) who proposed use of mitochondrial COI gene for species identification of animals and coined the term 'DNA barcoding'. This mitochondrial COI gene is used as standard DNA barcode for species identification as it shows higher interspecific distance than intraspecific divergence among and within species in addition to higher conserved amino acid sequence and possesses broad array of phylogenetic indications aiding in differentiation among less divergent species and phylogeographic clusters in single species (Brown et Later, this approach was widely followed by multiple researchers in the globe who tested this gene for its applicability for identification of marine fauna, Layton et al (2014) and Mikkelsen et al (2007) identified molluscs from Canada and four genera of Norwegian bivalves, respectively. However, since probabilities of contamination by mucopolysaccharides (Layton KKS et al, 2014;Skolov 2000) in marine clams are higher, this group of animals become quite complex for DNA barcode process and as a result, very less work has been done in molecular 1175 biodiversity of such species, particularly, in India.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…This mitochondrial COI gene is used as standard DNA barcode for species identification as it shows higher interspecific distance than intraspecific divergence among and within species in addition to higher conserved amino acid sequence and possesses broad array of phylogenetic indications aiding in differentiation among less divergent species and phylogeographic clusters in single species (Brown et Later, this approach was widely followed by multiple researchers in the globe who tested this gene for its applicability for identification of marine fauna, Layton et al (2014) and Mikkelsen et al (2007) identified molluscs from Canada and four genera of Norwegian bivalves, respectively. However, since probabilities of contamination by mucopolysaccharides (Layton KKS et al, 2014;Skolov 2000) in marine clams are higher, this group of animals become quite complex for DNA barcode process and as a result, very less work has been done in molecular 1175 biodiversity of such species, particularly, in India. Moreover, difficulties in collection of these species exist due to marine habitats that are not easy to reach generating poor understanding of clam biodiversity around coastal region especially in India, although it has got ample coastal area of 7,516 km (Venkataraman and Wafar, 2005), no efficient initiative has been taken for identifying and analyzing clam biodiversity (Pawar, 2012) through DNA barcoding resulting into inadequate specimen and sequence data repository and lack of robust species level identification data along with genetic lineage studies leading to low scale scientific understanding of cryptic and endangered species.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%